2021
DOI: 10.1177/00368504211013247
|View full text |Cite
|
Sign up to set email alerts
|

Pathologies associated with the mandibular third molar impaction

Abstract: To evaluate the associations of impaction patterns of mandibular third molars (M3Ms) with pathologies caused by them. In this study, 262 patients with 432 impacted M3Ms who referred in Shanghai Xuhui District Center were reviewed. The pathologies include pericoronitis, mandibular second molar (M2M) caries, and M2M distal periodontal pathology. The impaction patterns of M3Ms and the pathologies were examined, while the M2M outcomes after surgeries were evaluated. A χ2 test was used to analyze the data, with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 26 publications
4
22
0
2
Order By: Relevance
“…This last method provides more accurate results and allows the methodology of the study to be reproduced. In accordance with our findings, many previous studies have also shown that mesioangular impaction is the most common type of impaction [ 2 4 , 7 , 8 , 14 , 17 21 , 23 ]. On the other hand, some other previous reports demonstrated that the vertical type of MTM impaction is the predominant impaction type [ 6 , 22 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This last method provides more accurate results and allows the methodology of the study to be reproduced. In accordance with our findings, many previous studies have also shown that mesioangular impaction is the most common type of impaction [ 2 4 , 7 , 8 , 14 , 17 21 , 23 ]. On the other hand, some other previous reports demonstrated that the vertical type of MTM impaction is the predominant impaction type [ 6 , 22 , 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…A comparable prevalence rate was observed in Saudi Arabia [ 17 ]. However, lower [ 8 , 14 ] and higher [ 18 , 19 ] prevalence rates have been reported. It is possible that inconsistencies in prevalence may be attributed to the difference in mineralization rates of the MTM, tooth-to-jaw ratios, and physical maturity among the study samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations